Progress in pattern recognition, image analysis, computer vision, and applications : 21st Iberoamerican Congress, CIARP 2016, Lima, Peru, November 8-11, 2016, Proceedings /: 21st Iberoamerican Congress, CIARP 2016, Lima, Peru, November 8-11, 2016, Proceedings. (2017) - Unknown
No abstract available